POLITIK PENGELOLAAN LIMBAH MEDIS COVID-19 DI KOTA MATARAM NTB PADA TAHUN 2020-2021 (Jurnal Nawala Politika, 2022)
This research was attemped to resolve the implementation of Covid-19 medical waste management policies in Mataram, Nusa Tenggara Barat. The research entitled “The Politics of Covid-19 Medical Waste Management in Mataram, NTB in 2020-2021” observed the role of political actors at executive and legislative institutions in successing the implementation of the policies. However, the theory applied in analyzing this research is Rational Choice Theory by James S Coleman. Rational Choice Theory focused on the efforts of political actors in establishing the policies with the reinforcements of entire available resources to succeed the implementation of the policies. Moreover, the research method was descriptive qualitative by obtaining primary and secondary data. The data were obtain by interviews and related literature reviews. Further more, the results of the research showed that the roles of political actors at Public Health Office Mataram, Environment Department Mataram, Environment Department Mataram, and DPRD Commission V in implementing the policies were considered to be improved. Otherwise, the numbers of budget fund allocation, infrastructure development, waste transportation service, and incinerators were considered to be increased and optimized in order to accomplish the implementation of Covid-19 medical waste management policies run successfully.